The Role of the Government of East Jakarta City in the Control of TB-HIV and the Fulfillment of the Right to Health - Patricia Tanuwijaya; Endang Wahyati Yustina; Suwandi Sawadi (Universitas Katolik Soegijapranata Semarang, 2019)
TB-HIV eradication is one of Indonesia’s government role implementation to ensure the rights to health for its citizens. Jakarta Timur is the area in DKI Jakarta that has the highest number of TB cases and the second-highest number of HIV cases. This research is held to understand the regulation regarding the government’s role in TB-HIV eradication, implementation of government’s role in TB-HIV eradication, and factors that influence the implementation of the government’s role in TB-HIV eradicationThe research was conducted in the Jakarta Timur area, throughout health care offices and institutions. This study used a sociological juridical approach with analytical descriptive specifications. The data used are primary data through interviews and observation, also secondary data through field and literature studies. The study used the purposive sampling method which includes TB-HIV patients and healthcare providers in health care facilities. The result of the study indicates that regulation regarding the Jakarta Timur government’s role in TB-HIV eradication has been created however separately, HIV regulation in Peraturan Daerah DKI Jakarta No. 5 Tahun 2008 and TB regulation in Peraturan Gubernur DKI Jakarta No. 28 Tahun 2018. Moreover, the collaborative regulation that has been created in the form of Surat Edaran Suku Dinas Kesehatan Kota Administrasi Jakarta Timur No. 50053/1.772.11, is not legally binding. Thus, the Government’s role in eradicating TB-HIV still encounters few factors that hinder its implementation thus the rights to health haven’t entirely fulfilled. Influencing factors are juridical, sociological, and technical factors. The juridical factors are the existence of regulation in TB-HIV eradication, however separately and the lack of legal binding in Surat Edaran to regulate TB-HIV eradication. The sociological factors are lack of patients’ medication compliance, healthcare provider’s stigma and violation of medical confidentiality. The technical factors are the TB-HIV collaboration team that hasn’t been arranged in health care facilities, overlap in TB-HIV reporting mechanism, availability of medication and funding that rely on donor’s contribution.